Self-supporting ultrathin three-dimensional lithium metal negative electrode material and preparation method thereof
Through the combination of nitrogen-doped carbon nanofibers/reduced graphene oxide three-dimensional composite material and Li3N layer, the problem of dendrite growth and energy density of lithium metal batteries is solved, and ultra-thin lithium metal with high conductivity and high energy density is achieved The negative electrode material improves the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202411240670.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-20
AI Technical Summary
Lithium metal batteries have dendrite growth problems, resulting in unstable circulation and low energy density. The existing ultra-thin lithium metal negative electrode materials preparation methods have problems such as poor machining, high cost, and poor conductivity.
Using nitrogen-doped carbon nanofiber/reduced graphene oxide 3D composite material as a self-supporting substrate, Li3N layer is generated through in-situ reaction, forming an ultra-thin three-dimensional structure, shortening the transmission path of Li+, improving conductivity and reactivity, and in the electrode The surface generates a Li3N rich artificial SEI interface layer.
Effectively inhibit the growth of lithium dendrites, improve the charge transfer rate, reduce lithium losses, improve the energy density and cycle stability of lithium metal batteries, and achieve high safety and long life.
Smart Images

Figure HDA0005029155530000011 
Figure HDA0005029155530000012 
Figure HDA0005029155530000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a self-supporting ultra-thin three-dimensional lithium metal negative electrode material and a preparation method thereof. Background Art
[0002] Lithium metal has a higher theoretical specific capacity (3860mAh g -1 ), lower electrode potential (-3.040V vs. standard hydrogen electrode) and good conductivity, making it the most promising negative electrode material for the next generation. However, lithium metal batteries have serious dendrite growth problems and are difficult to cycle stably for a long time. Therefore, people are committed to developing many emerging strategies to solve the problem of lithium dendrite growth and improve the safety and cycle life of lithium metal batteries. In recent years, although the research on lithium metal batteries has made significant progress, most of the research has focused on solving the problems of Li dendrites and low coulombic efficiency (CE).
[0003] Practical lithium metal batteries (LMBs) require an area capacity of less than 4 mAh cm -2 The thin lithium metal foil and the common lithium transition metal oxide positive electrode (area capacity of 3-4 mAh cm -2 ) pairing, which requires the thickness of lithium metal to be ≤20μm. In addition, in the first cycle of conventional lithium-ion batteries, SEI spontaneously forms on the negative electrode, resulting in a decrease in active Li and capacity (≤1mAhcm -2 ) loss, in order to achieve 100% initial Coulombic efficiency (ICE), a thinner Li metal foil (thickness ≤ 5μm) is often required to achieve the ideal Li compensation, that is, to achieve precise pre-lithiation. Therefore, the preparation of ultra-thin lithium metal foil is very important to improve the energy density of lithium metal batteries to match commercial cathodes.
[0004] Existing research strategies for ultrathin lithium metal anodes include: (1) Mechanical rolling: Lithium metal is soft and viscous, and can be processed into sheets through a simple rolling process, and can even be further rolled to 5μm; however, self-standing ultrathin metal lithium foil is soft and viscous, and has poor machinability; in addition, rolling easily leads to plastic deformation, resulting in the reorientation or redistribution of lithium crystals, or even shape changes, which will further introduce the risk of dendrite growth in lithium metal batteries (LMBs); (2) Electrochemical deposition is a feasible method for preparing micron-thin lithium on a conductive substrate, and the amount of deposited lithium can be achieved by controlling the deposition time or current density; however, the thickness, uniformity, flatness, and density of the lithium obtained by this method are affected by the electrolyte formulation, supporting substrate materials, and operating factors, and the high cost limits its practicality; (3) Molten lithium scraping or adsorption. The melting point of metallic lithium is lower than 180.5℃, and molten lithium has flowable characteristics and a smooth surface. It has strong plasticity in its properties (surface tension, viscosity, wettability), and can adapt to a series of liquid engineering methods to manufacture lithium foil. Currently, commonly used three-dimensional materials such as carbon cloth, copper foam and nickel foam have large surface areas and excellent three-dimensional structures, but they also face problems such as poor conductivity and high cost. When molten lithium is adsorbed, it is easy to cause problems such as thick electrode sheets, excessive adsorption of lithium metal, and low battery energy density. Therefore, it is very important to prepare an ultra-thin three-dimensional material with good conductivity, low cost, high energy density and high specific surface area. Summary of the invention
[0005] The main purpose of the present invention is to provide a self-supporting ultra-thin three-dimensional lithium metal negative electrode to solve the problems of low energy density and waste of lithium resources in lithium metal batteries. The ultra-thin three-dimensional structure shortens the Li + The presence of heteroatoms on the carbon surface can improve the reactivity and conductivity, thereby increasing the charge transfer rate. At the same time, the three-dimensional layered structure carbon material can effectively alleviate the volume expansion problem of lithium metal during the cycle. The preparation method involved is relatively simple and has good repeatability, which is suitable for popularization and application.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A self-supporting ultra-thin three-dimensional lithium metal negative electrode material comprises a nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material, lithium metal loaded in the three-dimensional composite material, and a Li3N layer.
[0008] Furthermore, the Li3N layer is on one side of the self-supporting ultra-thin three-dimensional lithium metal negative electrode material and has a thickness of 5 to 10 μm.
[0009] Furthermore, the Li3N layer is obtained by infusing molten lithium into the nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material to react in situ to generate Li3N, which migrates toward the upper surface under heating conditions.
[0010] In the above scheme, the diameter of the nitrogen-doped carbon nanofibers is 20 to 50 nm, and the diameter of the reduced graphene oxide sheets is 0.3 to 10 μm.
[0011] In the above solution, the thickness of the nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material is 10 to 50 μm.
[0012] Furthermore, the self-supporting ultra-thin three-dimensional lithium metal negative electrode material of the present invention first uses pyrrole and graphene oxide as main raw materials for ice bath polymerization reaction, calcination, to form a self-supporting three-dimensional material based on nitrogen-doped carbon nanofibers and reduced graphene oxide, and then pours molten lithium into it to load metallic lithium and react and migrate in situ to generate a Li3N layer.
[0013] The preparation method of the above-mentioned self-supporting ultra-thin three-dimensional lithium metal negative electrode material (NCF / rGO / Li3N) specifically comprises the following steps:
[0014] 1) adding pyrrole (Py) monomer to an aqueous solution of graphene oxide, adding an oxidant and a surfactant, and performing a polymerization reaction under ice bath conditions, wherein polypyrrole and graphene nanosheets are cross-linked with each other during the reaction to avoid stacking of graphene nanosheets, and the post-reaction solution is vacuum filtered and freeze-dried to obtain a polypyrrole / graphene oxide material;
[0015] 2) calcining the obtained polypyrrole / graphene oxide material under a protective atmosphere to obtain a nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material (NCF / rGO);
[0016] 3) placing the three-dimensional composite material obtained in step 2) in molten lithium and performing high-temperature molten lithium deposition to obtain the self-supporting ultra-thin three-dimensional lithium metal negative electrode material.
[0017] In the above scheme, the concentration of graphene oxide is 3 to 5 mg / mL.
[0018] Optionally, the graphene oxide is obtained by dispersing 1.5 to 2.5 g of GO in 500 mL of pure water and then ultrasonically dispersing it for 24 to 72 hours.
[0019] Furthermore, the flake diameter of the graphene oxide is 0.3-10 μm.
[0020] In the above scheme, the volume ratio of the pyrrole monomer and graphene oxide in step 1) is 1:(1-10).
[0021] In the above scheme, the oxidant can be ammonium persulfate, potassium perchlorate or ferric chloride.
[0022] In the above scheme, the molar ratio of the oxidant to the pyrrole monomer in step 1) is (1-1.5):1.
[0023] In the above scheme, the surfactant can be selected from hexadecyltrimethylammonium bromide, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.
[0024] In the above scheme, the mass ratio of the surfactant to the pyrrole monomer in step 1) is (1-1.5):4.
[0025] In the above scheme, the temperature of the ice bath reaction in step 1) is 0-5°C, and the reaction time is 1-2h.
[0026] Preferably, in the vacuum filtration, the amount of the post-reaction solution introduced is 1 / 3 to 2 / 3 of the volume of the filtration funnel.
[0027] In the above scheme, the temperature used for freeze drying is -40 to -10°C and the vacuum degree is 13 to 40Pa.
[0028] In the above scheme, the calcination protective atmosphere in step 2) can be Ar or Ar / H2.
[0029] In the above scheme, the calcination step in step 2) includes: first heating to 200-300°C at a rate of 2-4°C / min, keeping warm for 1-2h, then heating to 500-600°C at a rate of 4-6°C / min, keeping warm for 3-4h.
[0030] Furthermore, the second heating rate is higher than the first heating rate.
[0031] In the above scheme, the temperature used for high-temperature molten lithium deposition in step 3) is 200-350° C., and the deposition time of the three-dimensional carbon material in the molten lithium is 2-6 minutes.
[0032] In the above scheme, the mass ratio of the three-dimensional composite material to molten lithium in step 3) is 1:(5-10).
[0033] In the above solution, the thickness of the self-supporting ultra-thin lithium metal negative electrode material is 10 to 50 μm.
[0034] The self-supporting ultra-thin three-dimensional lithium metal negative electrode prepared according to the above scheme includes a nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material, lithium metal loaded therein, and a Li3N-rich artificial SEI interface layer formed by in-situ reaction between the nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material and the upper surface of the electrode.
[0035] The present invention provides a self-supporting ultra-thin lithium metal material to solve the problems of large amount of lithium waste and low energy density caused by the serious mismatch between the capacity of existing lithium metal negative electrode and positive electrode. The present invention uses reduced graphene oxide as the substrate, introduces nitrogen-doped carbon nanofibers derived from polypyrrole under ice bath conditions to prevent the stacking of graphene, can quickly filter and form a film, provides a large amount of three-dimensional space, effectively alleviates the volume expansion effect, and effectively solves the problem that the traditional graphene oxide film forming process easily leads to dense stacking of graphene; then molten lithium is perfused, and the nitrogen-doped carbon nanofibers react with molten lithium to form Li3N in situ and migrate to the electrode surface under heating conditions to form a Li3N-rich artificial SEI interface layer (allowing lithium ions to be freely embedded and de-embedded, but preventing electrons from passing), enhancing the wettability of lithium, and guiding Li + Uniform deposition can inhibit the growth of lithium dendrites; in addition, the constructed ultra-thin three-dimensional structure can effectively shorten the Li + The presence of heteroatoms on the carbon surface can improve the reactivity and conductivity, thereby increasing the charge transfer rate; ultra-thin lithium metal three-dimensional materials with controllable thickness reduce lithium loss and improve the energy density of lithium metal batteries.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1) In the ice bath reaction, pyrrole monomers are well dispersed in the aqueous solution of graphene oxide. During the polymerization process, polypyrrole is adsorbed on the graphene oxide nanosheets. The nitrogen-doped carbon nanofibers derived from polypyrrole are cross-linked with graphene and have a strong interaction. The constructed ultra-thin three-dimensional structure also effectively shortens the Li + The presence of heteroatoms on the carbon surface can improve the reactivity and conductivity, thereby increasing the charge transfer rate; in addition, nitrogen-doped carbon nanofibers can prevent the stacking of graphene, and the resulting three-dimensional carbon material has high conductivity and huge lithium storage space.
[0038] 2) The present invention uses a self-supporting three-dimensional carbon material as a substrate with controllable thickness; during the molten lithium infusion process, the thickness of the ultra-thin three-dimensional substrate does not change, and a Li3N artificial interface layer can be generated in situ on the electrode surface, which is beneficial to enhance the wettability of lithium; Li3N has excellent Li + The electrical conductivity and low diffusion barrier enable Li + Rapid downward migration effectively avoids the deposition of lithium on the electrode surface, thereby effectively inhibiting the growth of lithium dendrites; the three-dimensional layered structure provides sufficient buffer space for the deposition / stripping of lithium, which can effectively alleviate problems such as volume expansion during the cycle.
[0039] 3) The thickness of the three-dimensional carbon material prepared by the present invention is controllable, and the thinnest can be controlled at about 10 μm. Moreover, the thickness remains basically unchanged after adsorbing molten lithium, which can greatly reduce the amount of negative electrode lithium. The ultra-thin lithium metal negative electrode is matched with the commercial positive electrode, which effectively improves the energy density and is conducive to the realization of high-safety, long-life, and high-energy-density lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The scanning electron micrographs of NCF / rGO obtained in Example 1 are (a) low magnification and (b) high magnification conditions;
[0041] Figure 2 This is the transmission electron microscopy image of NCF / rGO obtained in Example 1;
[0042] Figure 3 TEM image of nitrogen-doped carbon nanofibers in NCF / rGO obtained in Example 1;
[0043] Figure 4 (a) Cross-sectional SEM image of NCF / rGO / Li3N obtained in Example 1 and (b) linear scan image of N element from top to bottom in the direction of arrows;
[0044] Figure 5 X-ray diffraction patterns of NCF / rGO / Li3N, NCF / rGO, NCF, rGO and GO obtained in Example 1;
[0045] Figure 6 The lithium storage cycle rate performance diagram of the lithium metal battery is assembled by matching the NCF / rGO / Li3N obtained in Example 1 of the present invention and the electrode materials obtained in Comparative Examples 1 to 4 with LiFePO4 positive electrode materials. DETAILED DESCRIPTION
[0046] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
[0047] Example 1
[0048] A self-supporting ultra-thin three-dimensional lithium metal anode material (NCF / rGO / Li3N) is prepared by an ice bath method and a high-temperature molten lithium infusion method, specifically comprising the following steps:
[0049] 1) 80 mL of 4 mg / mL graphene oxide aqueous solution was measured, 20 μL of pyrrole monomer and 0.08 g of hexadecyltrimethylammonium bromide (CTAB) were added thereto, and the resulting mixed solution was stirred at 0-5° C. for 30 min; then ammonium persulfate solution was added dropwise (0.068 g of ammonium persulfate (APS) was dissolved in 1 mL of water and mixed evenly); after continuing to stir for 30 min, 20 mL of the resulting mixed solution was taken and placed in a 60 mL Buchner funnel for suction filtration and freeze-drying to form a film;
[0050] 2) calcining the membrane material obtained in step 1) under an argon atmosphere, specifically comprising: firstly heating to 250°C at a rate of 3°C / min, keeping the temperature for 1.5h, then heating to 550°C at a rate of 5°C / min, keeping the temperature for 3.5h, to obtain NCF / rGO;
[0051] 3) In an argon glove box with an O2 and H2O content of less than 0.01 ppm, lithium metal is heated to 350°C to become a molten state, and then the NCF / rGO obtained in step 2) is placed on liquid metal lithium for 3 minutes (the mass ratio of the three-dimensional carbon material to the molten lithium is 1:(5-10)). Under high temperature conditions, the NCF / rGO reacts with the molten lithium to generate Li3N and migrates to the upper surface; after the reaction is complete, it is naturally cooled to room temperature, and then punched out into a circular electrode sheet with a diameter of 8 mm with a puncher for use, thereby obtaining an NCF / rGO / Li3N composite negative electrode.
[0052] The scanning electron microscope image of the three-dimensional material NCF / rGO obtained in step 2) of this embodiment is shown in Figure 1 .Depend on Figure 1 It can be seen from a that the obtained NCF / rGO presents a three-dimensional layered structure with folds and undulations, a large specific surface area, a large amount of lithium storage space, and a thickness of about 27 μm. Figure 1 b It can be seen that under a high-power electron microscope, nitrogen-doped carbon nanofibers are in a nanowire-like structure, attached to graphene nanosheets, and cross-linked to form a lamellar composite three-dimensional structure.
[0053] The transmission electron microscope image of the three-dimensional material NCF / rGO obtained in step 2) of this embodiment is shown in Figure 2-3 From the figure, it can be seen that nitrogen-doped carbon nanofibers are attached to graphene nanosheets, and the average diameter of the carbon nanofibers is about 32.2nm.
[0054] The scanning electron microscope image of the composite negative electrode NCF / rGO / Li3N obtained in step 3) of this embodiment is shown in Figure 4 a. After the high-temperature molten lithium infusion experiment, metallic lithium was injected into the three-dimensional layered space without obvious deformation. Figure 4In b, the obtained composite electrode is linearly scanned for N elements from top to bottom as indicated by the arrows. The content of N elements gradually decreases from the upper surface to the lower surface of the electrode, indicating that the N element is mainly concentrated on the upper surface. During the heating process, Li3N formed at the interface between metallic lithium and the three-dimensional material NCF / rGO spontaneously migrates to the upper surface to form an artificial interface layer rich in Li3N with a thickness of about 7 μm.
[0055] The X-ray diffraction pattern of NCF / rGO / Li3N obtained in this example is shown in Figure 5 The characteristic peaks of NCF and rGO can be observed in the XRD diffraction pattern of NCF / rGO, which strongly proves the successful composite of NCF and rGO. The XRD diffraction pattern of NCF / rGO / Li3N after molten lithium infusion clearly shows the characteristic peaks of Li3N and Li, proving that in the high-temperature molten lithium infusion experiment, NCF / rGO reacts with molten lithium to generate Li3N, which is beneficial to enhance the wettability of lithium and guide Li + Uniform deposition inhibits the growth of lithium dendrites.
[0056] Example 2
[0057] A self-supporting ultra-thin three-dimensional lithium metal negative electrode material, the preparation method of which is substantially the same as that of Example 1, except that: the amount of pyrrole monomer added in step 1) is 40 μL; by increasing the ratio of pyrrole to graphene oxide, the thickness of the obtained electrode sample is increased to 30 to 40 μm.
[0058] Example 3
[0059] A self-supporting ultra-thin three-dimensional lithium metal negative electrode material, the preparation method of which is substantially the same as that of Example 1, except that: in step 1), the concentration of graphene oxide is 3 mg / mL; by reducing the concentration of graphene oxide, the thickness of the obtained electrode sample can be reduced to 10 to 20 μm.
[0060] Example 4
[0061] A self-supporting ultra-thin three-dimensional lithium metal negative electrode material, the preparation method is roughly the same as that of Example 1, except that: the volume of the filtered solution in step 1) is 30 mL; the thickness of the obtained self-supporting ultra-thin three-dimensional lithium metal negative electrode material can be controlled by increasing the volume of the filtered solution, and the thickness is increased to 35-45 μm.
[0062] Comparative Example 1
[0063] A three-dimensional lithium metal negative electrode material (rGO / Li), the preparation method of which comprises the following steps:
[0064] 1) Take 20 mL of 4 mg mL graphene oxide aqueous solution, place it in a 60 mL Buchner funnel for vacuum filtration, and freeze-dry to form a film;
[0065] 2) calcining the membrane material obtained in step 1) under an argon atmosphere, specifically comprising: firstly heating to 250°C at a rate of 3°C / min, keeping the temperature for 1.5h, then heating to 550°C at a rate of 5°C / min, keeping the temperature for 3.5h, to obtain rGO;
[0066] 3) In an argon glove box with an O2 and H2O content of less than 0.01 ppm, lithium metal is heated to 350°C to become a molten state, and then the rGO obtained in step 2) is placed on liquid metal lithium for 3 minutes (the mass ratio of the three-dimensional carbon material to the molten lithium is 1:(5-10)); after it is completely reacted, it is naturally cooled to room temperature, and then punched out into a circular electrode sheet with a diameter of 8 mm with a puncher for use, thereby obtaining an rGO / Li composite negative electrode.
[0067] Comparative Example 2
[0068] A two-dimensional lithium metal negative electrode material (N-rGO / Li3N), the preparation method of which comprises the following steps:
[0069] 1) 80 mL of 4 mg / mL graphene oxide aqueous solution was measured, 5 μL of pyrrole monomer and 0.02 g of hexadecyltrimethylammonium bromide (CTAB) were added thereto, and the resulting mixed solution was stirred at 0-5° C. for 30 min; then ammonium persulfate solution was added dropwise (0.068 g of ammonium persulfate (APS) was dissolved in 1 mL of water and mixed evenly); after continuing to stir for 30 min, 20 mL of the resulting mixed solution was taken and placed in a 60 mL Buchner funnel for suction filtration and freeze-drying to form a film;
[0070] 2) calcining the membrane material obtained in step 1) under an argon atmosphere, specifically comprising: firstly heating to 250°C at a rate of 3°C / min, keeping the temperature for 1.5h, then heating to 550°C at a rate of 5°C / min, keeping the temperature for 3.5h, to obtain N-rGO;
[0071] 3) In an argon glove box with an O2 and H2O content of less than 0.01 ppm, lithium metal is heated to 350°C to become a molten state, and then the N-rGO obtained in step 2) is placed on liquid metal lithium for 3 minutes (the mass ratio of the composite material to the molten lithium is 1:(5-10)). Under high temperature conditions, N-rGO reacts with molten lithium to generate Li3N; after the reaction is complete, it is cooled to room temperature and then punched out into a circular electrode sheet with a diameter of 8 mm with a puncher for use, thereby obtaining a N-rGO / Li3N composite negative electrode.
[0072] Comparative Example 3
[0073] A commercial lithium sheet with a thickness of 100 μm and a diameter of 8 mm was used as the lithium metal negative electrode material.
[0074] Comparative Example 4
[0075] A self-supporting ultra-thin three-dimensional lithium metal anode material (NCF / rGO / Li3N-A), the preparation method of which specifically comprises the following steps:
[0076] 1) NCF / rGO was prepared according to the method described in Example 1;
[0077] 2) In an argon glove box with an O2 and H2O content of less than 0.01 ppm, lithium metal is heated to 350°C to become a molten state, and then the NCF / rGO obtained in step 1) is placed on liquid metal lithium for 1 min (the migration effect of Li3N is changed by controlling the contact reaction time between the membrane material and the molten lithium) (the mass ratio of the three-dimensional carbon material to the molten lithium is 1:(5-10)), and under high temperature conditions, NCF / rGO reacts with molten lithium to generate Li3N; after the reaction is complete, it is naturally cooled to room temperature, and then punched out into a circular electrode sheet with a diameter of 8 mm with a puncher for use, thereby obtaining an NCF / rGO / Li3N-A composite negative electrode.
[0078] The NCF / rGO / Li3N electrode material obtained in Example 1 and the electrode materials described in Comparative Examples 1 to 4 were assembled into full batteries using the same method with LiFePO4 positive electrode materials to test their electrochemical performance. Figure 6 The results show that the introduction of the self-supporting ultra-thin three-dimensional material and the Li3N artificial interface layer of the present invention can effectively improve the battery capacity and rate performance.
[0079] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A self-supporting ultra-thin three-dimensional lithium metal negative electrode material, characterized in that: The invention comprises a nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material, lithium metal loaded in the three-dimensional composite material and a Li3N layer.
2. The self-supporting ultra-thin three-dimensional lithium metal negative electrode material according to claim 1, characterized in that: The diameter of the nitrogen-doped carbon nanofiber is 20-50 nm, and the diameter of the reduced graphene oxide sheet is 0.3-10 μm.
3. The self-supporting ultra-thin three-dimensional lithium metal negative electrode material according to claim 1, characterized in that: The thickness of the nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material is 10 to 50 μm.
4. The method for preparing a self-supporting ultra-thin three-dimensional lithium metal negative electrode material according to claim 1, characterized in that: The following steps are involved: 1) adding pyrrole monomer to an aqueous solution of graphene oxide, adding an oxidant and a surfactant, performing a polymerization reaction under ice bath conditions, and vacuum filtering and freeze-drying the solution after the reaction to obtain a polypyrrole / graphene oxide material; 2) calcining the obtained polypyrrole / graphene oxide material under a protective atmosphere to obtain a nitrogen-doped carbon nanofiber / reduced graphene oxide three-dimensional composite material; 3) placing the three-dimensional composite material obtained in step 2) in molten lithium and performing high-temperature molten lithium deposition to obtain the self-supporting ultra-thin three-dimensional lithium metal negative electrode material.
5. The preparation method according to claim 4, characterized in that: In step 1), the volume ratio of the pyrrole monomer to graphene oxide is 1:(1-10).
6. The preparation method according to claim 4, characterized in that: Step 1) The temperature of the ice bath reaction is 0-5°C, and the reaction time is 1-2h.
7. The preparation method according to claim 4, characterized in that: Step 2) The calcination step includes: firstly heating to 200-300°C at a rate of 2-4°C / min and keeping the temperature for 1-2h; then heating to 500-600°C at a rate of 4-6°C / min and keeping the temperature for 3-4h.
8. The preparation method according to claim 4, characterized in that: Step 3) The temperature used for high temperature molten lithium deposition is 200-350° C. and the deposition time is 2-6 min.
9. The preparation method according to claim 4, characterized in that: Step 3) The mass ratio of the three-dimensional composite material to molten lithium is 1:(5-10).
